Analisis Biaya Strategis Dengan Metode Activity Based Costing Pada UMKM Kerupuk Kulit Lombok - Adhitya Bayu Suryantara; Animah Animah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
Activity-oriented cost analysis is crucial to determining the activities that provide added value and those that do not add value to the company. The results of this analysis can be the basis for company decisions in determining strategic steps that can provide a competitive advantage. This study aims to analyze the strategic costs of Pade Angen, a cowhide cracker company, using the activity- based costing (ABC) method. The method used is the descriptive method. The results of this study indicate that the cost of goods manufactured for the original variant is IDR 66,472 and the stick variant is IDR 65,798. The selling price of the company follows the market price of IDR 90,000 - IDR 95,000. Referring to the condition of similar companies and industries, the selling price can be maintained provided that the company needs to take strategic steps that can provide an advantage to become cost leadership, such as investing in assets and human resources in order to increase productivity and modernize the production process